2020
DOI: 10.3390/nu12020305
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Coconut Oil and Epigallocatechin Gallate on the Levels of IL-6, Anxiety and Disability in Multiple Sclerosis Patients

Abstract: Background: Due to the inflammatory nature of multiple sclerosis (MS), interleukin 6 (IL-6) is high in blood levels, and it also increases the levels of anxiety related to functional disability. Epigallocatechin gallate (EGCG) decreases IL-6, which could be enhanced by the anti-inflammatory effect of high ketone bodies after administering coconut oil (both of which are an anxiolytic). Therefore, the aim of this study was to assess the impact of coconut oil and EGCG on the levels of IL-6, anxiety and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 48 publications
(53 reference statements)
1
37
0
1
Order By: Relevance
“…Moreover, several studies promoted the association between EGCG (300 µg, 2/die, by oral gavage, for 50 days) and other natural products, such as glatiramer acetate in EAE model [ 36 , 37 ], or coconut oil in MS patients [ 38 ]. In all these studies synergistic effects of the combination therapy were registered.…”
Section: Epigallocatechin-3-gallate (Egcg) In Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several studies promoted the association between EGCG (300 µg, 2/die, by oral gavage, for 50 days) and other natural products, such as glatiramer acetate in EAE model [ 36 , 37 ], or coconut oil in MS patients [ 38 ]. In all these studies synergistic effects of the combination therapy were registered.…”
Section: Epigallocatechin-3-gallate (Egcg) In Autoimmune Diseasesmentioning
confidence: 99%
“…In all these studies synergistic effects of the combination therapy were registered. EGCG and glatiramer acetate can improve the expression of both brain-derived neurotrophic factor (BDNF) and beneficial cytokines in CNS [ 36 ], and promote an increase in HO-1 expression level [ 37 ], whereas, in MS patients, EGCG (800 mg/die, orally, for 4 months) plus coconut oil improved anxiety and disability by decreasing IL6 serum level [ 38 ]. The clinical trials using EGCG in MS patients are shown in Table 1 .…”
Section: Epigallocatechin-3-gallate (Egcg) In Autoimmune Diseasesmentioning
confidence: 99%
“…The Special Issue “Nutrition and Fitness: Mental Health” of Nutrients includes four original articles [ 6 , 7 , 8 , 9 ] and three systematic reviews [ 10 , 11 , 12 ]. The first original article assessed the interconnections between specific quality of life domains (assessed with Short Form-36 [SF-36]) in 716 consecutive female and male patients with obesity and high or low physical performance using an innovative statistical analysis based on network approach [ 6 ].…”
mentioning
confidence: 99%
“…The third original article randomly allocated 51 patients with multiple sclerosis to 800 mg of epigallocatechin gallate (EGCG) and 60 mL of coconut oil or placebo for four months [ 7 ]. Both groups followed the same isocaloric Mediterranean diet.…”
mentioning
confidence: 99%
See 1 more Smart Citation